THE MODEL OF SUPPORT AND PROMOTION SYSTEM FOR DEVELOPMENT OF THE STAFF COMPETITIVENESS IN MODERN ENTERPRISE AS LEARNING ORGANIZATION - Katane, Irena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Since Latvia is member of the European Union, the importance of our society’s competitiveness and each its member's competitiveness is becoming even more important as the society of Latvia and each individual lives in a social space and the space of the global economy. Latvia must ensure the development of a knowledge based, democratic and socially integrated society. The development of competitiveness of Latvian society and the national economy must be ensured. It has been already acknowledged that an effective means for promoting competitiveness is lifelong and lifewide education, therefore enterprises and other various institutions are becoming learning organizations that promote the professional development and competitiveness of their staff in the context of knowledge society in general. The competitiveness of an enterprise to a great extent is dependent on the support and promotion system of the staff competitiveness. The aim of the article is to make public the results of theoretical research, describing the worked out Model of Support and Promotion System for Development of the Staff Competitiveness in Modern Enterprise as Learning Organization. The designed model as such is a system of cooperation that contains four basic components of the interaction: personnel management, career counselling, mentoring and specialist's competitiveness which is a central component in this model.